Engaging transnational expertise: creating Sowa Rigpa supplements between South Asia and Europe - Mundelius, Patricia; Sprisevska, Julija (Frontiers in Human Dynamics, 2025)
Attempts to facilitate Sowa Rigpa practice in European countries are fairly recent and mostly happen under precarious circumstances, especially since the restrictive legal environment severely limits access to Sowa Rigpa medicinal preparations. Another issue is the incompatibility of common Sowa Rigpa pharmaceutical preparations in the form of powders and pills with modern lifestyles and tastes that, simple as it may seem, presents a major practical challenge for Tibetan medicine in the west. To remedy these limitations and incompatibilities, some more innovative ways of medicine production emerge that are supposed to increase accessibility. Looking at small-scale transnational collaborations between practitioners, laboratories, and companies as complex multi-sited entanglements, this paper follows the emergence of Daknang Herbal Products as a low-key industrial aspiration between Latvia and Nepal that attempts to realize calls for innovation and seeks to explore novel paths of engaging Sowa Rigpa medicinal preparations as food supplements in European contexts. By examining Daknang’s path toward the establishment of Sowa Rigpa pharmaceuticals as self-medicated reformulated extracts produced in Europe, this paper addresses the questions to what extent Sowa Rigpa medicines need to be transformed to enter western food supplement markets, and what kind of concerns and moral discourses about ‘negative aspirations’ surround the innovation of established forms of medicinal preparations. The aim is to show that looking at transnational business collaborations offers interesting perspectives for the Asian medicine industry that tend to be overlooked due to their small-scale nature, but which are nevertheless involved in the innovation of Asian medicines for global markets.